Memristive perovskite solar cells towards parallel solar energy harvesting and processing-in-memory computing. Issue 18 (26th July 2022) - Rogdakis, Konstantinos; Loizos, Michalis; Viskadouros, George; Kymakis, Emmanuel
Abstract : Use a single memristive perovskite solar cell device for performing both solar energy harvesting and light-triggered synaptic functionalities. Abstract : The heterogeneity of peculiar ions and carriers observed in hybrid organic/inorganic materials is the source of their emergent cross-coupled light and electric field tuneable functions with potential utility in novel opto-electronic applications. Notably, mixed halide perovskites (HPs) have been used as active layers in high performing perovskite solar cells (PSCs) that led to efficient solar energy harvesting. Their rich dynamics enabled by inherently coupled ionic and electronic degrees of freedom have also led to the demonstration of optoelectronic memristors that emulate synaptic- and neural-like dynamics. Consequently, a printable single material stack fabricated at low temperature combining both solar energy harvesting and memristive functionalities attainable at low switching voltages would constitute a transformational breakthrough. In this study, we have demonstrated an inverted PSC with an average power conversion efficiency (PCE) of ∼17% that with appropriate electric biasing procedure exhibits stable resistance switching characteristics at low voltages without losing its PCE performance even after thousands of switching cycles (hereafter this device is termed as MemPVCell). In particular, the MemPVCell demonstrates a high resistance state (HRS) to low resistance state (LRS) ratio of up to 10 5 and light-tunable switching cycles in the millisecond regime with an endurance of 3 × 10 3 cycles with no detectable HRS/LRS ratio drop. During state retention tests, the HRS exhibits no change in time, while the LRS gradually increases resulting in an overall HRS/LRS ratio retention of up to 3600 s with less than a 30% drop of its initial value in the optimum device configuration. Corresponding PCE performance was monitored after using multiple dc resistance switching loops and pulsed endurance cycles, demonstrating full PCE recovery to its initial value within a few minutes of rest. Complementary transient electrochemical impedance spectroscopy (EIS) measurements supported the MemPVCell switching effects. Aiming at further improving the device performance, modifications of MemPVCell's layered structure were investigated, a process that allowed identification of each layer's impact on the parallel photovoltaic and memristive switching characteristics. As a proof of concept towards neuromorphic circuits, basic synaptic functionalities tunable by light are demonstrated such as potentiation and depreciation protocols, short-term plasticity (STP) and long-term plasticity (LTP) effects and associated spike-timing dependent plasticity (STDP).